Coumarins of Peucedanum baicalense and cytotoxic activity of some isolated coumarins - Ganbaatar, J; Shults, EE; Petrova, TN; Shakirova, MM; Otgonsuren, D; Munkhbat, E; Badamkhand, D; Tolstikov, GA; Batsuren, D (Mongolian Journal of Chemistry, 2014)
DOI: http://dx.doi.org/10.5564/mjc.v13i0.155 Mongolian Journal of Chemistry Vol.13 2012: 23-27